74 INTRAUTERINE GROWTH RETARDATION ALTERS EXPRESSION OF INSULIN-LIKE GROWTH FACTOR 1 IN FEMALE RAT THYMUS. Issue 1 (1st January 2007) - Zarbock, Z.; Jeffs, S. A.; McKnight, R. A.; Jenkins, S. L.; Lane, R. H.
Abstract : Background: Intrauterine growth retardation (IUGR) predisposes human infants and children to infectious diseases. We have previously shown that IUGR decreases the overall number of lymphocytes and alters T-cell phenotype. IUGR has also been shown to affect males to a greater degree than females. The exact mechanisms underlying these effects are unknown; however, the growth factor insulin-like growth factor 1 (IGF-1) is known to play a significant role in thymic development and lymphocyte proliferation. Additionally, IGF-1 levels in other organ systems are altered by IUGR. Furthermore, IGF-1 has several splice variants, which are preferentially expressed due to epigenetic mechanisms known to be active in IUGR. Objective: We therefore hypothesized that IUGR would decrease thymic size and alter IGF-1 mRNA expression and its splice variants in male and female rat thymus. Methods: Bilateral uterine artery ligation was performed on pregnant Sprague-Dawley rats to induce IUGR. Thymus tissue was harvested from IUGR and sham controls and weighed at d0 and d21. mRNA levels of the IGF-1 transcription start sites P1 and P2, as well as splice variants IGF-1A and IGF-1B, were quantified with real-time RT-PCR. Results: At d0, male IUGR rat thymus had an average weight of only 0.0073 g ± 0.001 compared with sham at 0.0138 g ± 0.002 ( p < .05, n = 5). d0 IUGR female thymus weighed 0.0075 g ± 0.0017 vs sham 0.012 g ± 0.0016 ( p < .05, n = 6). Consistent with these findings, female IUGR rats at d0 showed increases in IGF-1 transcription initiation at P1 and P2, as well as an increase in the transcript encoding the IGF-1B peptide ( p < .05). d21 females also showed an increase at the IGF-1A peptide (p < .05). Conversely, male IUGR rats at d0 did not show a significant difference in IGF-1 transcription initiation or splice variation. d21 IUGR males also did not show significant changes in IGF-1. Conclusion: The overall expression of IGF-1 was increased in IUGR female rat pups at d0 and the splice variant IGF-1A at d21. There were no significant changes in IGF-1 expression in male IUGR rat pups at d0 or d21. We know that IGF-1 is involved in the proliferation of lymphocytes and is increased in female IUGR rats and female lymphocyte phenotype and number are less affected by IUGR. We speculate that the increased IGF-1 levels and splice variants in females may explain why their immune systems are less severely affected by IUGR.